Synthesis and Biological Activity of Polyketones-System Based on m-Methylanisole using Nitrobenzene as Solvent - Patel, R.K.; Rawal, B.S.; Patel, R.M. (Asian Journal of Chemistry, 2012)
Polyketones were prepared by condensing chloroacetyl chloride/1,2-dichloroethane/dichloromethane with m-methylainsole in the presence of anhydrous aluminium chloride in nitrobenzene. The resin samples were characterized by an IR spectral study, measurement of their number average molecular weight by vapour pressure osmometry, TGA and DSC. All the polymers were tested for their biological activity against bacteria (B. subtilis and P. fluorescens) fungi (A. niger and T. longibachioatum), and yeast (R. minuta and S. cerevisiae).